A High‐Performance Rotational Energy Harvester Integrated with Artificial Intelligence‐Powered Triboelectric Sensors for Wireless Environmental Monitoring System. Issue 10 (21st April 2022) - Shrestha, Kumar; Maharjan, Pukar; Bhatta, Trilochan; Sharma, Sudeep; Rahman, Muhammad Toyabur; Lee, Sanghyun; Salauddin, Md; Rana, SM Sohel; Park, Jae Y.
Abstract : The prevailing energy harvester utilizes a convectional magnet that limits the output power due to the imperfect coupling of the flux linkage and the leakage of the magnetic fluxes away from the coil. Herein, a circular Halbach array magnet comprising the arc magnets is proposed as a high‐performance rotational energy harvester for preventing flux leakage by concentrating the magnetic flux in a particular path. The Halbach magnet is made up of eight individual arc magnet segments that are kept apart by 1 mm to induce a fourfold increase in magnetic flux density over a conventional magnet. The proposed rotational energy harvester can deliver an exceptional 603.2 W m −3 power density, which is attributed to a three times increase in the power density. The harvested power is utilized to charge a 30 mAh battery for driving a complete IoT system for the development of self‐powered wireless environmental monitoring systems. Furthermore, an intelligent system is designed using cutting‐edge artificial intelligence (AI) technology which accounts for Mxene/P(VDF‐TRFE)‐based triboelectric sensor output data and considers different weather parameters to accord a high accuracy of 99% in wind speed prediction. Abstract : A circular Halbach array‐based rotational energy harvester is proposed that generates a high output power that is utilized for the realization of the self‐powered environmental monitoring system. The triboelectric nanogenerators based on MXene/P(VDF‐TRFE) exhibit excellent robustness and durability with a wind sensitivity of 13.6 μA ms −2 .